Предмет: Математика,
автор: НеоРыбка
-3(3m-5n)-4(-2m+7n) при n=0,1; m=-0,2
упростить и решить
Ответы
Автор ответа:
0
-3(3m-5n)-4(-2m+7n)= -9m+15n+8m-28n=-m-13n=0,2-13*0,1=0,2-1,3=-1,1
Автор ответа:
0
=-m-13n попустила
Автор ответа:
0
подчеркни одной чертой -9m и +8m
Автор ответа:
0
а двумя чертами +15n и -28n
Автор ответа:
0
это однородные члены
Похожие вопросы
Предмет: Химия,
автор: balakinruslan69
Предмет: Математика,
автор: zhannamukhatova671
Предмет: История,
автор: Аноним
Предмет: Математика,
автор: valyha861